Differences Between General Neurologists and Multiple Sclerosis Specialists in the Management of Multiple Sclerosis Patients: A National Survey - Kurtuncu, Murat; Tuncer, Asli; Uygunoglu, Ugur; Caliskan, Zeynep; Kokenli Paksoy, Aysenur; Efendi, Husnu; Sagduyu Kocaman, Ayse; Ozcan, Cemal; Terzi, Murat; Turan, Omer Faruk; Saip, Sabahattin; Karabudak, Rana; et al. (AVES, 2019)
Introduction: The management of multiple sclerosis (MS) has become more complicated after the introduction of new diagnostic and treatment options. Despite the abundance of guidelines, the experience of physicians still plays a major role in the management of patients. This study aimed to define differences in behavior patterns between general neurologists (GNs) and MS specialists (MSSs). Methods: We conducted a survey of 36 questions to 318 neurologists, including 33 MSSs. The survey covered topics including laboratory investigations, pregnancy, and treatment. Results: Our study found many differences between GNs and MSSs in terms of management, the most important being treatment initiation and switching. GNs had a tendency to initiate treatment later than MSSs however, they tended to switch treatment faster. Our study also showed that GNs ordered magnetic resonance imaging (MRI) more frequently than MSSs, even if patients were clinically stable. Moreover, although GNs more frequently relied on MRI, they did not consider brain atrophy as an important measure in the follow-up of their patients. Furthermore, GNs considered replacement therapy less often than MSSs, even in patients with vitamin D deficiency. Discussion: Our study revealed important discrepancies between the management patterns of GNs and MSSs in MS patients. These findings suggest the need for a national education program for GNs on MSSs.
Keywords: Multiple sclerosis; general neurologists; multiple sclerosis specialists; management differences